Workers' Constructions of the "Good" and "Bad" Advocate in a Domestic Violence Agency. Issue 3 (27th May 2018) - Jury, Ang; Thorburn, Natalie; Weatherall, Ruth
ABSTRACT: Grassroots activist organizations are heavily reliant on workers' willingness and commitment to give of themselves. Organization expectations accordant with this are often embedded with organizational cultures and climates, which then tend to reinforce behaviors that threaten sustainable well-being. To find out how this might manifest in our own grassroots, domestic violence-focused agency, the authors surveyed 111 workers and interviewed 12. Pervasive cultural norms of selflessness and toughness led to a collective construction of what constitutes "good" advocates and "bad" advocates. The authors therefore focus their discussion on the paramountcy of promoting acceptance of emotionality beyond clients to the workforce itself.